Recurrent IDH2 Mutations in Salivary Gland Striated Duct Adenoma Define an Expanded Histologic Spectrum Distinct From Canalicular Adenoma - Rooper, Lisa M.; Agaimy, Abbas; Assaad, Adel; Bal, Munita; Eugene, Henrietta; Gagan, Jeffrey; Nonogaki, Hiro; Palsgrove, Doreen N.; Shah, Akeesha; Stelow, Edward; Stöhr, Robert; Thompson, Lester D. R.; et al. (American Journal of Surgical Pathology, 2023)
Striated duct adenoma (SDA) is a rare salivary gland neoplasm defined by histologic similarity to normal striated ducts. However, doubt persists about whether SDA represents a genuine entity distinct from canalicular adenoma and if a malignant counterpart exists. This study aims to evaluate the molecular underpinnings of SDA to clarify its pathogenesis and classification. We identified 10 SDA and 2 tumors called low-grade adenocarcinoma not otherwise specified that were retrospectively recognized to resemble SDA. All cases showed recurrent histologic features including (1) discrete monophasic tubules, (2) tall columnar eosinophilic cells, (3) monotonous oval nuclei, and (4) scant fibrous stroma, and most were positive for S100 protein (91%), SOX10 (80%), and CK7 (80%). Although 1 case was previously called adenocarcinoma based on interdigitation with normal acini, this pattern was also seen in some SDA, and likely does not indicate malignancy; the significance of growth surrounding nerve in 1 other case is less clear. Targeted sequencing identified IDH2 R172X mutations in all 8 cases with sufficient tissue, with positivity for IDH1/2 mutation-specific immunohistochemistry in 9 cases stained. In contrast, 5 canalicular adenomas lacked IDH2 mutations or other oncogenic alterations. Overall, IDH2 R172X mutations are a defining feature of SDA that, in combination with its recognizable pathologic profile, confirm it is a unique entity separate from canalicular adenoma. IDH1/2 mutation-specific immunohistochemistry may provide a convenient tool to facilitate diagnosis. Both morphology and IDH2 mutations raise parallels between SDA and breast tall cell carcinoma with reverse polarity.
CRIS-Team WoS Importer:2023-03-17